2020
DOI: 10.3390/diagnostics10050286
|View full text |Cite
|
Sign up to set email alerts
|

Whole Exome Sequencing with Comprehensive Gene Set Analysis Identified a Biparental-Origin Homozygous c.509G>A Mutation in PPIB Gene Clustered in Two Taiwanese Families Exhibiting Fetal Skeletal Dysplasia during Prenatal Ultrasound

Abstract: Skeletal dysplasia (SD) is a complex group of bone and cartilage disorders often detectable by fetal ultrasound, but the definitive diagnosis remains challenging because the phenotypes are highly variable and often overlap among different disorders. The molecular mechanisms underlying this condition are also diverse. Hundreds of genes are involved in the pathogenesis of SD, but most of them are yet to be elucidated, rendering genotyping almost infeasible except those most common such as fibroblast growth facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…This report describes the prenatal findings of the rare disease of DDSH and shows that the application of WES to heterogeneous diseases, such as SD, enables the discovery of underlying genetic defects. Of note, the homozygous HSPG2 mutation detected may imply a founder effect in the Taiwanese population, which we noted previously in several monogenic diseases such as autosomal recessive renal tubular dysgenesis, osteogenesis imperfecta Type IX and aromatic L‐amino acid decarboxylase deficiency 6 .…”
Section: Figuresupporting
confidence: 55%
“…This report describes the prenatal findings of the rare disease of DDSH and shows that the application of WES to heterogeneous diseases, such as SD, enables the discovery of underlying genetic defects. Of note, the homozygous HSPG2 mutation detected may imply a founder effect in the Taiwanese population, which we noted previously in several monogenic diseases such as autosomal recessive renal tubular dysgenesis, osteogenesis imperfecta Type IX and aromatic L‐amino acid decarboxylase deficiency 6 .…”
Section: Figuresupporting
confidence: 55%
“…Notably, a few earlier reports from Taiwan had pointed out that the mutant allele c.857-619_1269 + 243delinsTTGCCTTGC of the AGT gene is very likely to be a founder variant in the Chinese population, which may aid in the prompter identification of the molecular pathology in that rapid trio-WEs case (Ma et al, 2019;Tseng et al, 2020). Such founder effect alleles are not uncommon in the Chinese population and had been reported previously at other inherited disorders such as the c.509G > A/p.G170D mutation of the PPIB gene causing the osteogenesis imperfecta IX in the Chinese population, and the way to estimate the mutation dating was also reported (Chang et al, 2020;Zhu et al).…”
Section: Editorial On the Research Topic Emerging New Tests And Their Impact Upon The Practice Of Reproductive Geneticsmentioning
confidence: 88%
“…Shared haplotype was delineated by identifying the homozygous SNPs surrounding the pathogenic variant detected in the proband. We included data reported in patients from the Taiwan region ( Chang et al, 2020 ) as well as the SNP data of the 11 carriers found in the Chinese cohort. The founder effect was identified by taking individuals without the c.509G > A variant from the Chinese WES cohort as control.…”
Section: Methodsmentioning
confidence: 99%
“…Jiang et al reported the first Chinese OI-IX case with a compound heterozygous variant in PPIB ( Jiang et al, 2017 ). Chang et al reported two fetuses with a homozygous PPIB variant (c.509G > A/p.G170D) from the Taiwan region) ( Chang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%